Energy efficiency practices in selected facility management organizations in Johannesburg - Alister Anthony, Phooko Bopape, Thabethe Nokukhanya (en, 2016)
Energy efficiency

Facility management
adopting these strategies and rated the lowest were policies and regulations of energy efficiency standards. In current energy efficiency practices it is uncovered that occupant engagement and education is considered least, amongst the survey questions. This study recommends that businesses disregard the initial financial implications of adopting energy efficient strategies in light of the long term benefits that will see their investment returned and more and also to engage with end users as they could also lead to better facilities management with the information they can provide. This study also suggests that awareness of some practices can also improve the facilities management practices in the Johannesburg area.
Keywords: University of the Witwatersrand